Energy value of a low-digestible carbohydrate, NUTRIOSE FB, and its impact on magnesium, calcium and zinc apparent absorption and retention in healthy young men - Vermorel, M.; Coudray, C.; Wils, D.; Sinaud, S.; Tressol, J. C.; Montaurier, C.; Vernet, J.; Brandolini, M.; Bouteloup-Demange, C.; Rayssiguier, Y. (European journal of nutrition, 2004)
Long-term consumption of imbalanced diets, poor in dietary fibres, resulted in the prevalence of several nutritional pathologies. However, low digestible carbohydrates (LDC) have many beneficial effects, especially on energy intake, digestive physiology, and mineral absorption. To determine the digestive effects of a LDC, called NUTRIOSE FB, its metabolisable energy (ME) value, and its effects on mineral absorption in humans. Ten healthy young men were fed for 31 d periods a maintenance diet supplemented with either dextrose or the LDC at a level of 100 g DM/d, in six equal doses per d according to a cross-over design. After a 20 d adaptation period, food intake was determined for 11 days using the duplicate meal method, and faeces and urine were collected for 10 d for further analyses. Ingestion of the LDC did not cause severe digestive disorders, except excessive gas emission, and flatulence and slight abdominal pain in some subjects for intakes above 50 g DM/d. Wet and dry stool outputs increased by 45 and 70%, respectively (P<0.02). In vitro enzymatic digestibility of the LDC was 15 (SD 1.5) %, and 9.2 (SD 8.3) % of the LDC was excreted in faeces (P<0.001). The ME value of the LDC was 14.1 (SD 2.3) kJ/g DM, that is 14 % less than the tabulated values of sucrose and starch. Its net energy value (NEV), estimated using three prediction equations, was 8.7, 8.9, and 11.4 kJ/g DM. Ingestion of the LDC significantly increased the relative apparent absorption of Mg, and Mg retention by 67% and 31 mg/d, respectively, tended to increase Ca apparent absorption (P=0.110) and Ca retention (P=0.059), but did not significantly alter Zn parameters. NUTRIOSE FB can be used as a "bulking" agent, and substituted up to 50 g/d for usual maltodextrins without causing digestive disorders in healthy subjects. It would reduce intestinal transit disorders and energy intake, and improve magnesium and calcium absorption and retention.